A contribution to understanding the primary moult of birds - Scott, Tanya (Department of Biological Sciences, 2024)
Moult is an essential component of the annual cycle of birds, along with breeding, and, if migratory, migration. The leading statistical model for the analysis of primary moult is the Underhill-Zucchini moult model. It estimates moult parameters (duration, the mean start date and its standard deviation). An objective of this thesis was to assemble all published results which had used the UnderhillZucchini moult and to examine the resulting database for patterns in the timing, duration and synchronisation of moult. A total of 242 analyses of 136 species were found. The initial analysis of the database generated two observations: firstly, that latitude played an important role in determining patterns of primary moult, and, secondly, that the available data were latitudinally, spatially across continents, and taxonomically not representative. These gaps in knowledge were too large to rectify within the confines of a single PhD thesis. The preliminary chapters of the thesis added 18 analyses, for 11 species, and have made a contribution towards representativity. Two of the preliminary chapters make substantive contributions to the methods of undertaking statistical studies of moult. A new moult index, the Relative Duration Index, is introduced. Moult studies are frequently undertaken by combining datasets collected in different years (or different places). This thesis contains the first practical application of a proposed method to identify which of the individual datasets have a large influence of the estimates of the moult parameters. Nine analyses extended the latitudinal range of studies southwards and were based on datasets assembled in New Zealand. These are the first analyses of primary moult using the UnderhillZucchini moult model from this country. For seven species, this thesis undertakes moult studies of a species in both its original country, the United Kingdom, and the country into which it had been introduced, New Zealand. These are the first analyses of primary moult of this kind. Preliminary patterns of moult strategies are discussed. Critical gaps in our understanding of primary moult are identified. Priorities for fieldwork and analysis are described in order that key gaps are filled and a global review of primary moult can be undertaken.